Analisis Stabilitas Lereng dan Alternatif Perkuatan Lereng di Jalan Trunojoyo, Kelurahan Songgokerto, Kecamatan Batu, Kota Batu, Jawa Timur, Berbasis Software Geo5 2020 Pro - Nugraha, Satria Aji Budi; Suwarno, Eko (Jurnal Ragam Pengabdian, 2026)
The slope along Trunojoyo Street, Songgokerto Sub-district, Batu City, connecting Batu City and Pujon, has a high landslide susceptibility due to its hilly topography and steep gradient, as demonstrated by a landslide event on April 9, 2026, which completely blocked the main transportation access for approximately three hours. This study aims to obtain landslide characteristic data, analyze the stability of the existing slope, and evaluate a reinforcement alternative in the form of a cantilever retaining wall using Geo5 2020 Pro software based on the Limit Equilibrium Method. Field observation using the Slope Stability Inventory Form showed that the slope has a height of 15.00 meters and a gradient of 80°, with a silty sand (SM) soil type. Analysis of the existing condition using the Mohr-Coulomb method produced a safety factor (SF) of 0.68, far below the minimum requirement of SNI 8460:2017 (SF ≥ 1.50), indicating a critical slope condition. Three design variations of an 11-meter cantilever wall were analyzed across five stability components using the Bishop method. The results showed that variation 3, a cantilever wall with two-tier terracing, was the most optimal design, being the only one that satisfied all safety criteria, with an overall stability SF of 1.52 and settlement of 15.40 mm, meeting the 16.5 mm maximum limit required by SNI 8460:2017.